2011
DOI: 10.2522/ptj.20100142
|View full text |Cite
|
Sign up to set email alerts
|

Boxing Training for Patients With Parkinson Disease: A Case Series

Abstract: Despite the progressive nature of PD, the patients in this case series showed short-term and long-term improvements in balance, gait, activities of daily living, and quality of life after the boxing training program. A longer duration of training was necessary for patients with moderate to severe PD to show maximal training outcomes. The boxing training program was feasible and safe for these patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(154 citation statements)
references
References 34 publications
6
141
1
6
Order By: Relevance
“…Improvements in 6MWT with shorter tango interventions have been reported previously. 26,43 Improvements in 6MWT have also been demonstrated with other exercise interventions including boxing 44 and treadmill training. 45 As with gait velocity, changes in 6MWT in the present study were much smaller than those reported following treadmill training, 46,47 but it is possible that the low intensity aerobic exercise provided through dance may have helped Tango participants to maintain 6MWT performance while Control participants declined.…”
Section: Physical Functionmentioning
confidence: 94%
“…Improvements in 6MWT with shorter tango interventions have been reported previously. 26,43 Improvements in 6MWT have also been demonstrated with other exercise interventions including boxing 44 and treadmill training. 45 As with gait velocity, changes in 6MWT in the present study were much smaller than those reported following treadmill training, 46,47 but it is possible that the low intensity aerobic exercise provided through dance may have helped Tango participants to maintain 6MWT performance while Control participants declined.…”
Section: Physical Functionmentioning
confidence: 94%
“…A variety of community exercise programs have been established for patients with PD (tandem biking, "Delay the Disease" [Zid], Tango, Mark West Dance for PD, PWR!Moves TM , Rocksteady Boxing, Tai Chi) [60][61][62][63][64][65]. Our quality assurance studies reinforce the benefits of specific, short term aerobic exercise protocols using different rehabilitation technologies to improve mobility and balance without exacerbating signs and symptoms of PD (e.g., pain).…”
Section: Characteristics Of Equipment/work Out* Nusteptm-vasper Altergrmentioning
confidence: 99%
“…With physical inactivity as a primary health problem in the elderly [14,[60][61][62][63][64][65][66][67][68], exercise must be a standard part of health care services not only for those that are aging but also for those with impairments associated with chronic neurological disease like PD. To enhance opportunities for physiological and neuromusculoskeletal change, exercise protocols should follow the principles of "overload" (e.g., speed, performance time, frequency, progressive difficulty) with adaptation to individual signs and symptoms and individual preferences [66,67].…”
Section: Characteristics Of Equipment/work Out* Nusteptm-vasper Altergrmentioning
confidence: 99%
“…Therefore, perhaps a regular exercise regimen in itself improves endurance in PD. 89 Sensorimotor agility exercise programs strive to incorporate several different types of functional balance training exercises (including tai chi, boxing, etc) to emphasize improved coordination, improved motor program selection, and improved sensory integration. 21 Gait/treadmill training has also been investigated for its effect on quality of life, improvement in gait stride, and balance.…”
Section: Types Of Physical Activity and Exercise Most Recently And Bementioning
confidence: 99%